The Effect of Cryptocurrency Returns and Cryptocurrency Volume on the Stock Price Index of Indonesia, Singapore, Thailand - Ami Putri Utami; Kartini Kartini (Ridwan Institute, 2023)
The title of this study is to analyze the effect of cryptocurrency returns and cryptocurrency volume on the stock price indices of Indonesia, Singapore and Thailand. This research was conducted using the panel data regression method by combining cross section data with time series data using Eviews software. This study uses cryptocurrency returns and volumes in a weekly period from 1 January 2018 to 31 December 2021 for 48 weeks for each country with a total of 144 data. The results of this study indicate that cryptocurrency returns have a significant positive effect on the stock price indexes of Indonesia, Singapore, and Thailand. and cryptocurrency volume has a significant positive effect on the stock price indices of Indonesia, Singapore and Thailand.